2021
DOI: 10.1001/jamainternmed.2021.2621
|View full text |Cite
|
Sign up to set email alerts
|

Association of Changes in Seasonal Respiratory Virus Activity and Ambulatory Antibiotic Prescriptions With the COVID-19 Pandemic

Abstract: The COVID-19 pandemic led to numerous measures to mitigate the spread of SARS-CoV-2, including cancellations of gatherings, closure of businesses and schools, social distancing, wearing face masks, and other hygiene measures. 1 These may have unintended positive associations with reducing other respiratory infections. As antibiotics are frequently inappropriately prescribed for viral respiratory diseases, 2 we hypothesized that a decreased respiratory virus incidence would be associated with reduced ambulatory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
21
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 5 publications
5
21
1
Order By: Relevance
“…We found that the COVID-19 pandemic was associated with a decrease in overall and inappropriate antibiotic prescriptions in Chinese primary care facilities, with immediate levels decreasing in March 2020, and increasing trends thereafter. Similar effects have been observed in other studies ( Buehrle et al, 2020 ; King et al, 2020 ; Lepak et al, 2021 ; Miller et al, 2021 ). The COVID-19 pandemic has brought about a wide range of changes in the structure of health services, health-seeking behaviors, and medication supplies ( Knight et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…We found that the COVID-19 pandemic was associated with a decrease in overall and inappropriate antibiotic prescriptions in Chinese primary care facilities, with immediate levels decreasing in March 2020, and increasing trends thereafter. Similar effects have been observed in other studies ( Buehrle et al, 2020 ; King et al, 2020 ; Lepak et al, 2021 ; Miller et al, 2021 ). The COVID-19 pandemic has brought about a wide range of changes in the structure of health services, health-seeking behaviors, and medication supplies ( Knight et al, 2021 ).…”
Section: Discussionsupporting
confidence: 91%
“…The COVID-19 pandemic has brought about a wide range of changes in the structure of health services, health-seeking behaviors, and medication supplies ( Knight et al, 2021 ). Measures implemented to prevent and control the spread of COVID-19, including social isolation, use of personal protective equipment, hand and environmental hygiene, and active identification and quarantine of close contacts, have been effective in reducing the incidence of other infectious diseases, thus indirectly reducing antibiotic prescriptions for both necessary and unnecessary use ( Buehrle et al, 2020 ; King et al, 2020 ; Parry et al, 2020 ; Knight et al, 2021 ; Lai et al, 2021 ; Lepak et al, 2021 ; Miller et al, 2021 ). Early in the pandemic, antibiotics and other anti-inflammatory agents were partially unavailable in pharmacies and primary care institutions in China, and physicians prescribed these drugs carefully, fearing delays in identifying potential COVID-19 patients because of patient self-medication or insufficient diagnostic capabilities in primary care facilities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Consistent with the outcomes that we found in our setting with more than 1,500 centres, rates of prescriptions and influenza and non-influenza virus detections decreased during the pandemic period. Nevertheless, non-influenza virus detections presented the strongest correlation with antibiotic use for ARTIs in that study [ 27 ].…”
Section: Discussionmentioning
confidence: 98%